How helping students design ethical metaverse platforms can lead to safety and wellbeing for all - Sundararajan, Binod; Sundarararjan, Malavika (Journal of Management and Business Education, 2025)
A lack of proximity and enhanced anonymity in virtual worlds seems to provide the license to Artificial Intelligence (AI) based metaverse users to misbehave. Bullying, abuse, spread of hatred and divisiveness and manipulations of minds in Metaverses are growing exponentially due to the speed and magnitude with which AI enabled bots in Metaverses can multiply and reproduce content. Online violence has begun spilling into the real world which is negatively impacting the psyche and wellbeing of children and young adults in society. Ethicists or well-meaning employees have spoken out against these violations in Metaverses. But we find many such ethics groups have been dissolved or silenced while employees who are whistleblowers are often fired, discredited, or dismissed. Business Ethics, Marketing, Management and Sustainability students are often asked to simply carry out an ethical analysis of cases and provide recommendations. While such processes have helped explore various ethical schools of thought, the application of these concepts to AI based metaverses seems less about what framework to apply and more about how to design a fail-proof system to protect the safety and wellbeing of all. Such an approach will make students more aware of the consequences of their choices and develop a sense of responsibility towards the wellbeing of all. The paper proposes the use of a case study of a hypothetical company that has a metaverse platform and the challenges it faces in addressing abuse and scandals on its platform. The paper also offers a detailed review along with the pros and cons of several ethical frameworks and puts forth two key questions to students asking them to design a metaverse platform that can, a) ensure the wellbeing, security, and safety of the users who are not even aware that their minds may be swayed and manipulated; and b) find a way to convince companies that create AI-based metaverses to adopt ethical frameworks. Sample answers are provided to help faculty work with students understand the importance of always designing products and services with personal and others’ well-being in mind rather than only making profits at the cost of people’s safety and security.